2020
DOI: 10.7717/peerj-cs.315
|View full text |Cite
|
Sign up to set email alerts
|

Immersive virtual environments and embodied agents for e-learning applications

Abstract: Massive Open Online Courses are a dominant force in remote-learning yet suffer from persisting problems stemming from lack of commitment and low completion rates. In this initial study we investigate how the use of immersive virtual environments for Power-Point based informational learning may benefit learners and mimic traditional lectures successfully. We examine the role of embodied agent tutors which are frequently implemented within virtual learning environments. We find similar performance on a bespoke k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 64 publications
(79 reference statements)
0
5
0
Order By: Relevance
“…Through 1:1 scale head movement, viewers can choose where to focus their attention as if physically present. Although 1 study from the University of Bath demonstrated similar student performance using real and virtual worlds, 19 others have reported benefits of applying iVR to education. These include better performance on cognitive tasks, increased engagement and attentiveness, decreased external distractions, reduced attrition rates and improved procedural learning.…”
Section: Discussionmentioning
confidence: 96%
“…Through 1:1 scale head movement, viewers can choose where to focus their attention as if physically present. Although 1 study from the University of Bath demonstrated similar student performance using real and virtual worlds, 19 others have reported benefits of applying iVR to education. These include better performance on cognitive tasks, increased engagement and attentiveness, decreased external distractions, reduced attrition rates and improved procedural learning.…”
Section: Discussionmentioning
confidence: 96%
“…Students show a higher motivation when the instructor expresses happiness. Fitton et al (2020) demonstrated that teaching in VR with an ECA tutor leads to the same student performance, engagement, and motivation as teaching in a real classroom with a real teacher. Students reported that they found it strange that the ECA did not show different facial expressions, which might indicate that this is an important non-verbal social cue in this scenario.…”
Section: Digital Humans As An Instance Of Embodied Conversational Age...mentioning
confidence: 89%
“…Hence, CAs can invoke such social reactions as well and have their social presence impacted by the social cues, affecting trust, user satisfaction, and the success of a long-term relationship between CA and a human (Feine et al, 2019). Social presence grows when a CA becomes more realistic due to factors including appearance and behavior, such as non-verbal cues (Fitton et al, 2020). The influence of appearance can be so strong that individuals may judge trustworthiness of an ECA based on whether its neutral face is more similar to happiness or anger, where the agent seems to be more trustworthy in the first case and less so in the second.…”
Section: Anthropomorphism and Social Cues In Ecamentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, students and teachers have been recommended to switch to online learning instead of face-to-face classes as usually occurs at various educational institutions ( Basilaia & Kvavadze, 2020 ). One type of this online learning is the virtual classroom that shares some characteristics with ordinary or traditional classrooms ( Basilaia & Kvavadze, 2020 ; Fitton, Finnegan & Proulx, 2020 ) such as flexibility, practicality, and accessibility to learning environments that are not limited by time or place ( Elbourhamy, Najmi & Elfeky, 2023 ; Elbyaly & Elfeky, 2023 ). Najran University in Saudi Arabia, as well as other educational institutions in other countries, could transfer to online learning and conduct virtual classrooms by providing its staff with an educational platform known as ‘Blackboard’, a system that enabled both students and faculty members to restore the whole content and requirements of any academic course.…”
Section: Introductionmentioning
confidence: 99%